2020
DOI: 10.1093/jamia/ocaa219
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physicians’ prescribing experience, work hours, and workload with prescription errors

Abstract: Objective We aimed to assess associations of physician’s work overload, successive work shifts, and work experience with physicians’ risk to err. Materials and Methods This large-scale study included physicians who prescribed at least 100 systemic medications at Sheba Medical Center during 2012–2017 in all acute care departments, excluding intensive care units. Presumed medication errors were flagged by a high-accuracy comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…This can be attributed to the fact that their partners were doctors (619 women, 63.9% vs. 598 men, 26.8%; p < 0.001) and that they were working full time (1334 women, 74.7% vs. 2629 men, 80.8%), as shown in Table 1 . In previous studies 27 – 30 , working hours were thought to be affected only by childbirth and childcare experience, however, this study proved that they were greatly affected by the occupation and working style of their partner. To support the generation with childcare experience, it is socially important to create a system that allows them to continue working without leaving the workforce.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…This can be attributed to the fact that their partners were doctors (619 women, 63.9% vs. 598 men, 26.8%; p < 0.001) and that they were working full time (1334 women, 74.7% vs. 2629 men, 80.8%), as shown in Table 1 . In previous studies 27 – 30 , working hours were thought to be affected only by childbirth and childcare experience, however, this study proved that they were greatly affected by the occupation and working style of their partner. To support the generation with childcare experience, it is socially important to create a system that allows them to continue working without leaving the workforce.…”
Section: Discussioncontrasting
confidence: 42%
“…Long working hours are an important factor to be considered under labor management because they can lead to burnout and a decline in job performance due to fatigue and lack of concentration 22 – 26 . While working hours are necessary for self-improvement as part of professional training, too long working hours leave little time for off-job training 27 . The prevalence of burnout among physicians is high globally, and it is important to prevent it.…”
Section: Discussionmentioning
confidence: 99%
“…Mistakes are more likely if staff need to rush while working and/or are anxious due to potentially unachievable workloads [33][34][35][36][37][38]. This may be due to difficult and complex operations, sick patients, the skill mix of the theatre team or routine operating theatre lists with large numbers of cases [39].…”
Section: Administrative Barriers: Operating Theatre List Planningmentioning
confidence: 99%
“…First, about work-life interference, when individuals can manage efficiently the boundaries between the professional and non-professional domains, work overload tends to decrease, and as a result, their mental health is not negatively affected (e.g., Charalampous, et al, 2022;Grant et al, 2019). At the same time, employees who can balance their work and family life tend to experience a greater ability to focus on the tasks at hand, and their job satisfaction and performance tend to increase (e.g., Karatepe, 2013;Leviatan, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when employees experience a continuous state of work overload tend to feel tired decreasing their motivation to perform effectively. Hence, the continuous excessive workload tends to lead to physical, mental, and behavioral problems (Khuong & Yen, 2016), such as psychosomatic complaints (e.g., Barriga Medina et al, 2021), counterproductive work behaviors (e.g., Karatepe, 2013;Kissi et al, 2019), and increased errors when performing the tasks (e.g., Leviatan et al, 2021), which in turn decreases the worker's ability to attain work goals (Tang & Vandenberghe, 2021). (2021) demonstrated that the key challenges experienced by teleworkers during the pandemic crisis were work-family interference, workload, and excessive monitoring from supervisors that negatively affected their well-being.…”
Section: The Relationship Between Telework and Work Overloadmentioning
confidence: 99%